PENDUGAAN FRONT DAN UPWELLING MELALUI INTERPRETASI CITRA SUHU PERMUKAAN LAUT DAN CLOROFIL-A DI PERAIRAN WAKATOBI SULAWESI TENGGARA - Domu Simbolon; Muslim Tadjuddah (Institut Pertanian Bogor, 2008)
The objectives of this study are to know the distribution of the sea surface temperature (SST) and clorophill-a concentration around Wakatobi waters Southeast Sulawesi, and to determine the location of thermal front and upwelling. Fishing activity would be more efficient and effective when fishing ground was recognized well to fishing vessel leaved from fishing base. One of the method to determine fishing ground is to studying of thermal front and upwelling phenomenon by using the SST and chlorophyl-a analysis.The observation of the sea surface temperature and chlorophill-a which detected by using satellite data can be used to forcast the thermal front and upwelling phenomenon, and then used to forecast the potential fishing ground. The mean of SST during west season was 27.5°C with clorophill-a concentration 1.35 mg/m³. While the mean of SST during west-east season 26.7°C with clorophill-a concentration was about 0.78 mg/m³. Thermal Front occured around Kapota reefs, Kaledupa reefs, Koromaha reefs and Koka reefs. Based on thermal front distribution the potential fishing ground of cakalang was located in the east of Wakatobi waters especially around Koromaha reefs and Koka reefs. Upwelling was not found during west season and west-east season.